2017
DOI: 10.1111/hequ.12118
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Organisations and Systems Back Together: Extending Clark's Entrepreneurial University

Abstract: Burton R. Clark's 1998 book, Creating Entrepreneurial Universities, has had a major impact on the field of higher education, especially internationally. In this paper, key aspects of Clark's conceptualisation of organisational pathways of transformation are identified, speaking to its theoretical and empirical contributions to higher education studies, policy and practice. In addition, the larger corpus of Clark's work is built on to offer avenues by which considerations of systems analysis and organisational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Herewith, the entrepreneurial academic can be described as an academic who enriches the income revenue of his/her institution as well as his/her personal income via scholarly business combining the commercialisation of research, consultation and external teaching services. However, as the response to the important question in the study of Rhoades and Stensaker (), ‘does individualistic entrepreneurial push of universities move them towards … the various public, community‐enhancing, nation‐building and larger social democratic purposes of higher education?’ (p. 138), it does not seem such an individualistic and competitive approach among entrepreneurial academics contributes to the composition of high public profile universities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herewith, the entrepreneurial academic can be described as an academic who enriches the income revenue of his/her institution as well as his/her personal income via scholarly business combining the commercialisation of research, consultation and external teaching services. However, as the response to the important question in the study of Rhoades and Stensaker (), ‘does individualistic entrepreneurial push of universities move them towards … the various public, community‐enhancing, nation‐building and larger social democratic purposes of higher education?’ (p. 138), it does not seem such an individualistic and competitive approach among entrepreneurial academics contributes to the composition of high public profile universities.…”
Section: Resultsmentioning
confidence: 99%
“…Herewith, the entrepreneurial academic can be described as an academic who enriches the income revenue of his/her institution as well as his/her personal income via scholarly business combining the commercialisation of research, consultation and external teaching services. However, as the response to the important question in the study of Rhoades and Stensaker (2017) Although several studies demonstrated that faculty's entrepreneurial activities negatively influence their teaching engagement (Lee & Rhoads, 2004;Provasi et al, 2012), their collaboration with external actors can create various opportunities such as updating their courses for recent expectations in the industry/business environment, bringing extra internship opportunities for their students or obtaining contracts for their research team that includes students as well. Therefore, modern universities tend to take scientific skills and external networks together into consideration during the appointments or promotions of academics.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…The most important processes which must be considered are teaching, research, managerial, logistical, commercialization, selection (for students, university professors and staff), funding and financial, networking and multilateral interaction processes (between students, university professors, staff, industrial researchers, entrepreneurial centres, industries, policy makers and society) (Salamzadeh et al, 2011). Rhoades expanded Clark's theories about entrepreneurial university by relating the considerations of systems analysis and organizational studies (Rhoades, 2017). According to Etzkowitz, becoming an entrepreneurial university takes place in three stages: University entrepreneur one: The university must determine its strategic direction, start acquiring the needed abilities, develop a facilitative legal framework and set its own priorities.…”
Section: Unique Framework Formentioning
confidence: 99%
“…For example, instructional designers are harbingers of social change (Schwier et al 2006). The ensuing blurring of roles where academic staff are only "but one group of many professional specialists involved in producing instructional materials" (Rhoades and Slaughter 2004, p. 49) generates concerns that traditional governance is undermined and academic jobs threatened, especially full-time academic positions (Poritz and Rees 2017;Rhoades and Stensaker 2017). On the other hand, there is the counterargument that professional staff are better equipped to handle some administrative tasks and their presence provides more time for academic to do their teaching and research roles (Bexley et al 2011).…”
mentioning
confidence: 99%